A review on the recycling of spent lithium-ion batteries (LIBs) by the bioleaching approach - Roy, Joseph Jegan (2021)
This review discusses the latest trend in recovering valuable metals from spent lithium-ion batteries (LIBs) to meet the technological world's critical metal demands. Spent LIBs are a secondary source of valuable metals such as Li (5%–7%), Ni (5%–10%), Co (5%–25%), Mn (5–11%), and non-metal graphite. Recycling is essential for the battery industry to extract valuable critical metals from secondary sources to develop new and novel high-tech LIBs for various applications such as eco-friendly technologies, renewable energy, emission-free electric vehicles, and energy-saving lightings. LIB waste is currently undergoing high-temperature pyrometallurgical or hydrometallurgical processes to recover valuable metals, and these processes have proven to be successful and feasible. These methods, however, are not preferable due to the difficulties in controlling the process, secondary waste produced, high operational cost, and high risk of scaling up. Biotechnological approaches can be promising alternatives to pyrometallurgical and hydrometallurgical technologies in metal recovery from LIB waste. Microbiological metal dissolution or bioleaching has gained popularity for metal extraction from ores, concentrates, and recycled or residual materials in recent years. This technology is eco-friendly, safe to handle, and reduces operating costs and energy demands. The pre-treatment process (material preparation), microorganisms used in the bioleaching of LIBs, factors influencing the bioleaching process, methods of enhancing the leaching efficiency, regeneration of electrode materials, and future aspects have been discussed in detail.